The deceivers - Haddix, Margaret Peterson; OverDrive, Inc. (New York : Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2020)
Told from separate viewpoints, as Finn, Emma, and Chess Greystone and Natalie Mayhew, ages eight to thirteen, continue their quest to rescue their mothers they must return to the alternate dimension where truth is illegal.
Electronic book.
Ages 8-12.
Grades 4-6.
Electronic reproduction.
Keywords: Brothers and sisters -- Fiction; Family life -- Fiction; Honesty -- Fiction; Supernatural -- Fiction; Missing persons -- Fiction; Advantage title -- Fiction; Electronic books